2016
DOI: 10.1097/md.0000000000005110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Leber's hereditary optic neuropathy patients prior to a gene therapy clinical trial

Abstract: Gene therapy may be a promising approach for the treatment of Leber hereditary optic neuropathy. The aim of this study was to evaluate patients with this condition who were recruited into an upcoming gene therapy clinical trial and to assess any changes in the detection parameters to provide support for the clinical trial. Sixteen patients with Leber hereditary optic neuropathy were evaluated using visual function tests 12 months before the initiation of gene therapy. Then, the results of visual acuity (VA), v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 25 publications
3
24
2
5
Order By: Relevance
“…Before the advent of gene therapy, there was no treatment for LHON that exhibited confirmed efficacy. Spontaneous visual recovery was observed in 4% to 25% of the patients with mutations at site 11 778 . Young age at onset, slow disease progression, mild degree of vision loss and thicker retinal nerve fibre layer were considered predictors of good visual acuity recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Before the advent of gene therapy, there was no treatment for LHON that exhibited confirmed efficacy. Spontaneous visual recovery was observed in 4% to 25% of the patients with mutations at site 11 778 . Young age at onset, slow disease progression, mild degree of vision loss and thicker retinal nerve fibre layer were considered predictors of good visual acuity recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous visual recovery was observed in 4% to 25% of the patients with mutations at site 11 778. 2,9,[14][15][16][17] Young age at onset, 18 slow disease progression, 19 mild degree of vision loss 3 and thicker retinal nerve fibre layer 20 were considered predictors of good visual acuity recovery. Analysis of the factors influencing spontaneous visual acuity recovery showed that baseline characteristics may also affect the visual acuity prognosis of LHON patients with mutations at site 11 778 who were treated with gene therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research, however, has ruled out the possibility of spontaneous vision recovery. First, 1 year before clinical treatment, patients with spontaneous VA were excluded, and the improvement of VA in 9 patients treated from 3 months after treatment started to increase with a similar trend [7, 9]. Second, Lam et al [20] also conducted an in-depth study of the effect of increased spontaneous vision on gene therapy.…”
Section: Discussionmentioning
confidence: 99%